Transformative Learning Through Nonformal Education At Social Rehabilitation Centers (Study At 4 Social Rehabilitation Centers Of South Sulawesi Province) - Fatmawati Gaffar; Sardin Sardin (STKIP Singkawang, 2025)
Transformative learning approach in social rehabilitation centers is an important basis in the process of developing people with social welfare problems (PMKS). This article discusses the transformative learning process through three main stages: disorienting dilemma, self examination, and planning a course of action. This process helps create changes in attitudes, behavior and skills that support the social function and independence of PMKS. The uses a qualitative with a case study type. The results of this research transformative learning process tissystematically designed in social rehabilitation centers has an impact on fundamental changes in clients characterized by the ability to recover from trauma so that they can significantly improve social function and independence.